Wybór najlepszych, ze względu na średnią, populacji normalnych - Cieślik, Joachim; Sitek, Mirosława (Polskie Towarzystwo Antropologiczne, 1987)
The work presents a method o f choosing the best normal population and a method of choosing the subset including the best normal population. In both cases the method depends on whether the variances are identical and known or not.
Selection of the best average normal populations